Uji Daya Terima dan Kandungan Gizi Abon Jantung Pisang dengan Penambahan Teri Nasi (Stolephorus sp) - Wahyuni Sammeng; Michran Marsaoly; Nilfar Ruaida (Poltekkes Kemenkes Maluku, 2023)
Banana flower contains more nutrition. This research is an experimental type of banana blossom processed into shredded 6 samples with the addition of anchovies, using 30 untrained panelists for organoleptic tests. A nutritional content test was carried out to assess protein, fat, carbohydrates, ash content, water content, calcium, zinc, and iron. The results showed that there were differences in acceptability at S1, S2, S3, S4, S5, and S6. In the preference test, the most preferred color is S6, the most preferred taste is S5, the most preferred aroma and texture is S6. The highest water in S3, the highest ash in S2, the highest protein in S6, the highest fat in S5, highest carbohydrate in S1, the highest calcium in S6, the highest zinc in S1 and highest iron in S2. The more anchovies were given in formula, the panelists liked it more and the protein, fat, calcium, and iron content was higher. Conversely, the more banana flower, the higher carbohydrate and zinc content. The water and ash content in shredded beef is affected by the processing. Suggested further research to assess the content of minerals and other vitamins in banana flower shredded products with the addition of anchovies.